Critical thinking in intellectual property law. Issue 5 (8th June 2020) - Azam, Monirul
Abstract : Purpose: This paper aims to evaluate how critical thinking be integrated in intellectual property (IP) law teaching. Design/methodology/approach: It used doctrinal methods based on existing pedagogical scholarship in the field of effective teaching and learning at the university level. Findings: It demonstrated how the use of critical thinking in IP law education could facilitate deeper understanding of IP law issues from different socio-economic, environmental, historical and political dimensions. Research limitations/implications: It is yet to be tested for practical application in other jurisdictions and students having background from diverse socio-economic and cultural settings. Practical implications: The application of critical thinking in IP law could help students to apply IP law from practical perspectives to meet societal objectives and business interests as well. Social implications: This will facilitate in broader societal understanding in using IP law to achieve sustainable development goals. Originality/value: Till date, little work has been undertaken on the use of critical thinking in IP law teaching. Therefore, this study tried to make a unique contribution to incorporate critical thinking in IP law education.